Research of the properties of renewable energy sources with battery electrode from new materials - Song Xueying; Tan Zhongfu; Li Yuanhuan (Functional Materials, 2017)
A new type of material is proposed for the electrodes of a storage battery with a high energy density and stable characteristics. The structure and electrochemical properties of the new material are analyzed under two different methods of production. The system of connection to the power system is analyzed, and the energy-saving system for optimization of the output power of renewable energy. The economic benefit of the proposed battery is analyzed. The results show that the energy storage system of the new anode material for the battery is technically and economically justified and can be used to solve a complex energy consumption problem.